INFODEMIOLOGY: USING GOOGLE TRENDS AS A RESEARCH TOOL DURING THE COVID-19 PANDEMIC - H. Morokhovets; Yu. Lysanets; I. Kaidashev (Проблеми екології та медицини)
The paper examines the prognostic potential of the Google Trends resource as one of the infodemiological tools that allows collecting and analyzing the frequency of search queries on the Internet. The aim of the research is to analyze the Cyrillic search queries on Google to study the dynamics of the development of COVID-19 in Ukraine in 2020-2022. The time interval of the study from 15.03.2020 to 23.02.2022 was determined by available official information on the incidence of COVID-19 in Ukraine. The data obtained from Google Trends, normalized relative to the country of study and time interval, was downloaded in *.csv format. Correlation between quantitative indicators was assessed using the Spearman rank correlation coefficient. The authors proposed a new direction to study the dynamics of the development of COVID-19, which relies on the analysis of the search for symptoms and names of medications to predict the course of the disease. It has been shown that Google Trends is an effective tool for the rapid collection of information on the state of morbidity in the country. The use of keyword searches not only allows us to predict the development of the disease but can also be an effective tool of pharmacoeconomics. The revealed regularities can be used in international epidemiological studies, taking into account national characteristics, the geographical location of the country, the impact of preventive restrictions, etc.